2019
DOI: 10.1021/acsbiomaterials.9b00562
|View full text |Cite
|
Sign up to set email alerts
|

Fish-Scale Collagen Membrane Seeded with Corneal Endothelial Cells as Alternative Graft for Endothelial Keratoplasty Transplantation

Abstract: The human corneal endothelium has limited regeneration capacity. Several methods have been developed in an attempt to repair it. Descemet stripping automated endothelial keratoplasty (DSAEK) is commonly performed on patients with endothelial dysfunction. However, donor demand far exceeds donor supply. Here, we prepared fish-scale collagen membrane (FSCM) and seeded it with CECs in preparation for corneal endothelial transplantation. The fish scales were decellularized, decalcified, and curved. The FSCM was ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…This approach can directly produce neurovascular structure in the infarct cavity and modulate inflammatory, scar, and neural stem cell responses in the adjacent brain. Li, KY et al seeded corneal en-dothelial cells (CEC) on fish scale collagen membrane (FSCM) and transplanted them [164]. After FSCM was implanted into the anterior chamber of rabbit cornea, it was found that the corneal transparency and thickness were normal at all time points, and no edema or turbidity was observed [164].…”
Section: Other Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can directly produce neurovascular structure in the infarct cavity and modulate inflammatory, scar, and neural stem cell responses in the adjacent brain. Li, KY et al seeded corneal en-dothelial cells (CEC) on fish scale collagen membrane (FSCM) and transplanted them [164]. After FSCM was implanted into the anterior chamber of rabbit cornea, it was found that the corneal transparency and thickness were normal at all time points, and no edema or turbidity was observed [164].…”
Section: Other Biomedical Applicationsmentioning
confidence: 99%
“…Li, KY et al seeded corneal en-dothelial cells (CEC) on fish scale collagen membrane (FSCM) and transplanted them [164]. After FSCM was implanted into the anterior chamber of rabbit cornea, it was found that the corneal transparency and thickness were normal at all time points, and no edema or turbidity was observed [164]. FSCM was suitable as a cell carrier for corneal transplantation.…”
Section: Other Biomedical Applicationsmentioning
confidence: 99%
“…to enhance hESC‐derived retinal pigment epithelial cells attachment to synthetic electrospun membranes drawing similar conclusions. [ 51 ] Hence, the requirement of surface modifications to use BNC as a cell culture substrate seems to be cell type‐dependent. This cell‐specificity has also been described by Pertile and colleagues [ 52 ] who reported that nitrogen plasma activation improved the affinity of microvascular cells and neuroblasts for BNC but had no effect on fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Li and coworkers applied the decellularization technique to develop decellularized fish-scale collagen membranes with adequate strength and transparency. 1 These membranes allowed corneal endothelial cells to attach and grow with tight cell conjugation and normal morphology. After the fish-scale collagen membranes were implanted into rabbit anterior chambers, corneal clarity and thickness remained normal throughout the course of examination.…”
mentioning
confidence: 99%
“…A good example of natural materials is fish scales, which are multilayered and well-oriented. Li and co-workers applied the decellularization technique to develop decellularized fish-scale collagen membranes with adequate strength and transparency . These membranes allowed corneal endothelial cells to attach and grow with tight cell conjugation and normal morphology.…”
mentioning
confidence: 99%